Problem Based Learning dalam Penguatan Literasi Matematis, Berpikir Kritis, dan Motivasi Belajar Siswa SMP: Problem-Based Learning in Strengthening Mathematical Literacy, Critical Thinking, and Learning Motivation of Junior High School Students - Lodiana Bees, Nene; Alifiani, Nurrisqi; Nurul Zahra, Dindah (Department of Mathematics Education, Faculty of Tarbiyah, Institut Agama Islam Negeri Parepare, 2025)
This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model on students' mathematical critical thinking skills, mathematical literacy, and learning motivation in mathematics. The method used in this research is a Systematic Literature Review (SLR). Data collection and analysis were conducted using the PRISMA method, which consists of four main stages: (1) Identification, (2) Screening, (3) Eligibility, and (4) Inclusion. The results of this study indicate that: (1) the Problem-Based Learning model is effective in improving students' mathematical critical thinking skills compared to other learning models; (2) the Problem-Based Learning model is effective in enhancing students' mathematical literacy; and (3) the Problem-Based Learning model is effective in increasing students’ motivation to learn mathematics.